2003
DOI: 10.1002/hup.493
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal variations in first lapses to smoking for nicotine patch users

Abstract: Amongst those not using nicotine replacement therapy (NRT), first lapses to smoking have been shown to be more common in the afternoons and evenings than the mornings. The present study investigated whether first lapses amongst those using 16 h nicotine patches follow a similar pattern. This is of interest because 16 h patches may not provide sufficient nicotine early in the morning to meet the needs of smokers. 200 male and female smokers attended a cessation programme combining behavioural support and 16 h n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Thus, greater morning use may reflect overall nicotine dependence. A second observation is that higher rates of relapse have been observed in afternoon and evening hours in those receiving behavioral support (Brandon et al, 1986;Shiffman et al, 1996) or behavioral support and NRT (Ussher and West, 2003). In the current study, greater nicotine use in the evening hours may be related to lower relapse only insofar as it indirectly indexes lower dependence.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Thus, greater morning use may reflect overall nicotine dependence. A second observation is that higher rates of relapse have been observed in afternoon and evening hours in those receiving behavioral support (Brandon et al, 1986;Shiffman et al, 1996) or behavioral support and NRT (Ussher and West, 2003). In the current study, greater nicotine use in the evening hours may be related to lower relapse only insofar as it indirectly indexes lower dependence.…”
Section: Discussionmentioning
confidence: 69%
“…In both smokers and non-smokers, mood and energy level tend to decline toward the end of the day (Adan and Sanchez-Turet, 2000;Adan et al, 2004). Ussher and West (2003) have suggested that greater behavioral support and increased nicotine replacement during the afternoon and evening hours might help offset diurnally related increased risk of relapse.…”
Section: Discussionmentioning
confidence: 97%